Fat necrosis of abdominal pannus following caesarean section in a woman with morbid obesity. (16th November 2010) - Chiswick, C; Cooper, ES; Norman, JE; Denison, FC
Abstract : The authors present the first case report of a patient with morbid obesity who developed fat necrosis of the abdominal pannus following caesarean section. The patient was a 40-year-old primigravida with a body mass index of 44 kg/m 2 . After a relatively uncomplicated antenatal course, she underwent an emergency caesarean section for delay in first stage of labour at 2 cm dilation after induction of labour at 37 weeks gestation for non-proteinuric hypertension. Her immediate post natal period was uncomplicated and she was discharged on day 7 following removal of staples and deep tension sutures. She represented 3 weeks later with a 4 cm necrotic ulcer, 10 cm superior and distinctly separate to the caesarean section wound which was well healed. An ultrasound scan demonstrated a cavity 6×6×20 cm within the pannus. The patient was systemically well and swabs were negative. She was managed conservatively with twice weekly review by a multidisciplinary team including surgeons and obstetricians. However, by 6 weeks postnatal the necrotic area had enlarged to 10×8 cm, had started to leak copious amounts of offensive fatty exudate and there was new onset of cellulitis. The pannus was therefore debrided twice leaving a 20×5×8 cm defect. At operation, there was extensive fat necrosis of the abdominal pannus. Vacuum assisted closure therapy was used for 4 weeks. The wound was completely healed by 5 months postpartum. Dependant oedema and retraction of the pannus at operation may increase the risk of fat necrosis in morbidly obese women undergoing caesarean section.